Three years of experience with medicated intrauterine device with copper (TCu-380A) at the National Hospital Loayza Archbishop - Escudero, Francisco (2015)
OBJETIVE. To know efficacy acceptability and causes of discontinuation in IUD users. SETING. Family Planning Service at ALAIH. MALTERIAL AND METHODS. During 1992-1994, 3706 TCu-380A IUDs were inserted to healthy patients, 3167 intergenesic, with prior information and normal gynecological exam; controls were monthly, semestral and annual to determine secondary effects and cause and date of discontinuation. Rates were estimated by year and total accumulation and reasons of discontinuation by life-table survival analysis. RESULTS. From 3167 women, 361 discontinued for different reasons, 1667 continued use and 1139 did not return to control. Discontinuation at three years was 24,8% per 100 woman-year use, because of pregnancy 1,10 (n=16), IUD expulsion 10,19 (n=148), pain 1,17 (n=17), abnormal vaginal bleeding 1,99 (n=29), pelvic infection 1,44 (n=21), personal reasons 8,73 (n=127), and medical reasons 0,19 (n=3); accumulated total conttinuity use rate was 75,1. CONCLUSIONS. Efficacy of TCu-380A IUD is similar to that reported by other investigators. Loss to follow-up is high, especially during the first year.